Improving Entrepreneurial Skills Through Training in Making Local Material-Based Reed Diffuser Aromatherapy for the Productive Age Community - I Nyoman Sudyana; Retno Agnestisia; Muhammad Irmawan; Risfiah Ruli Cahyani; Eka Jhonatan Krissilvio; Erwin Prasetya Toepak (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Habaring Hurung is one of the sub-districts in Bukit Batu District, Palangka Raya City, where most of the people work as farmers of vegetables and various types of flowering plants, such as Kenanga Flowers (Cananga odorata). However, the abundance of Kenanga flowers has not been utilized optimally by residents. Therefore, this service activity aims to improve entrepreneurial skills among people of productive age in Habaring Hurung Subdistrict by making reed diffuser aromatherapy products from Kenanga flowers. This service activity is carried out based on the ABCD method (asset-based community development) on September 4, 2023, at the Habaring Hurung Sub District Office Hall with 34 participants. The results showed that the activity participants stated the activity theme according to what was needed. Apart from that, the material presented is also easy to understand, so it can increase participants' knowledge and skills in processing Kenanga flower reed diffuser aromatherapy. This activity is expected to provide local residents with the knowledge and skills to utilize local materials in products of high economic and useful value.